ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR GANDUM INDONESIA DARI AUSTRALIA TAHUN 1997-2022 - Fadhitama Farhan Saputra; Setyowati, Eni (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Wheat imports are a problem that is still difficult to control in Indonesia because people still consume a lot of food made from wheat. This study objective to assess impact of wheat production, wheat consumption, and the currency conversion rate rupiah on wheat imports Indonesia from Australia in year 1997-2022 by applying the Domowitz-Elbadawi Error Correction Model (ECM) method. The finding from analysis concluded that wheat production, wheat consumption, and the currency conversion rate together has significance impact on wheat imports. Then the influence partially, it is known that wheat production for the time being has no impact wheat imports. In the long run, wheat production has a positive impact on wheat imports. Meanwhile, wheat consumption in the short term and long term has an impact positive on wheat imports. Then in a short period, the rupiah exchange rate does not influence wheat imports, while in the long term, rupiah exchange rate influence negative impact wheat imports. To reduce the level of Indonesian wheat imports from Australia, the government needs to increase local food production such as cassava as a substitute for wheat flour raw materials. Bank Indonesia is the authority that must maintain rupiah exchange rate stability so as not to fall for maintain Indonesia's economic survival.